Dolor musculoesquelético y capacidad funcional en adultos mayores de la parroquia Sacapalca del cantón Gonzanamá - Sarmiento Herrera, Stefany Carolina (2023)
In Ecuador, the elderly population in rural areas presents musculoskeletal pain, often minimized, causing possible complications and impaired functional capacity. Muscle pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage. The objective of this study was to know the degree of musculoskeletal pain intensity, to identify the state of functional capacity according to sex and age group, and to establish the relationship between both variables in the elderly of Sacapalca parish of Gonzanamá canton. A study with a quantitative approach, prospective vision, and cross-sectional cohort was applied, with a universe of 183 older adults who met the inclusion criteria. The adapted COPCORD questionnaire was used, including the VisualAnalogical Scale (VAS), where the degree of musculoskeletal pain intensity was assessed. In addition, the adapted HAQ-DI, with which the state of the functional capacity of the elderly, was assessed. Evidencing that musculoskeletal pain predominates in the male sex, with 56% (n= 104) between 65 to 74 years. The functional capacity is mainly altered in the male sex 32% (n=59); and in ages between 65 and 74 years 31% (n=58). A p < 0.0001 was obtained, showing a statistical relationship between the variables. Older adults who present musculoskeletal pain have impaired functional capacity, thus, the degree of intensity of musculoskeletal pain is related to the state of functional capacity in the study participants